End-of-life: old age in contemporary society, self-perception of aging and ‘An’ Islamic perspective - Rathor, Mohammad Yousuf; Ali Khan Khattak, Muhammad Muzaffar; Mohd Yusof, Nazri (International Journal of Human and Health Sciences, 2019)
Population aging is a global phenomenon which has important and far-reaching implications for many facets of human life. Although it is an achievement of public health policies and socioeconomic development; it is generally greeted with alarm as it is assumed that elderly will be ill and dependant due to age-related chronic diseases which will require long term care. Despite the fact that many older adults continue to work and contribute to the society, they are seen as a burden and a drain on resources, rather than as a resource in themselves. Ageism and discrimination towards elderly is prevalent at individual and institutional levels that affect their physical and mental health, putting them at risk of depression and social isolation. According to the World Health Organization’s (WHO) combatting ageism has great potential for achieving healthy ageing for all people as they age. Individual health and longevity is influenced by biological, environmental, and psychosocial factors, however modifiable risk factors are especially relevant as they are amenable to intervention. There is enough evidence that religiosity and spirituality (R/S) are among such factors which allow older adults to age in a more positive way. Further R/S activities are prevalent globally and elderly tend to have high rates of involvement in religious activities. Health benefits that may stem from R/S involvement could be important for the future of global health which suggests that they could be incorporated into the idea of positive ageing. Islamic perspective on old age is deeply rooted in the very texts of revelation and as such is divinely based. This review article intends to create awareness of the elderly on the ageing process, their status in the contemporary society and how by adopting positive attitude toward ageing they can enjoy better functional health, self-esteem and satisfaction in life.